Sosialisasi Potensi Pasar Kopi Lokal di Pasar Global bagi Komunitas Teman Kohi - Sophiana Widiastutie; Shanti Darmastuti; Mansur Juned (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Indonesia has long been known as the world's largest coffee producer. Original Indonesian coffee is also known to have the advantages of various varieties, qualities and flavors. The advantages of Indonesian coffee cannot be separated from the role of the coffee industry players. The role of local coffee industry players is important in encouraging the expansion of the Indonesian coffee market at the global level. In this regard, the team carried out community service activities (PkM) at the Komunitas Teman Kohi, one of the local coffee industry players whose members are members of the youth community and are engaged in coffee entrepreneurship. The socialization activity started with a dialogue with the Komunitas Teman Kohi, who are interested in discovering more about the local coffee market opportunities in the global market in terms of potential, challenges and strategies to enter the global market. In this activity, the team distributed pre-tests before conducting socialization and discussion activities about local coffee market opportunities, followed by filling out post-tests. In addition, to add insight from the participants, the team invited a source person to share experiences related to the opportunities and challenges in expanding the local coffee market. Through this activity, participants from the Komunitas Teman Kohi gained understanding and insight into the local Indonesian coffee market in the global market.